2002
DOI: 10.1177/0886260502017006004
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Risk Factors for Women's Sexual Victimization

Abstract: The purpose of this study was to examine a broad range of childhood experiences associated with risk for sexual assault victimization in adulthood. Childhood experiences hypothesized to enhance vulnerability for adult sexual victimization, including maltreatment experiences perpetrated by adults and children as well as family composition variables, were examined. A community sample of 277 women attending outpatient clinics at an urban hospital provided retrospective self-report regarding family composition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…In a study by Hetzel and McCanne (2005), participants with a history of CPA or a history of both CPA and CSA were more likely to report ASA than those with no prior abuse or a history of CSA only. Fewer studies have examined the impact of CEA on revictimization risk, though existing research suggests that a history of emotional abuse also confers risk for adolescent and adult sexual victimization (e.g., Stermac, Reist, Addison, & Millar, 2002; Zurbriggen, Gobin, & Freyd, 2010). In fact, a growing body of research suggests that diverse forms of childhood maltreatment can increase risk for revictimization (e.g., Widom et al, 2008).…”
Section: Expanding Revictimization Risk Beyond Csamentioning
confidence: 99%
“…In a study by Hetzel and McCanne (2005), participants with a history of CPA or a history of both CPA and CSA were more likely to report ASA than those with no prior abuse or a history of CSA only. Fewer studies have examined the impact of CEA on revictimization risk, though existing research suggests that a history of emotional abuse also confers risk for adolescent and adult sexual victimization (e.g., Stermac, Reist, Addison, & Millar, 2002; Zurbriggen, Gobin, & Freyd, 2010). In fact, a growing body of research suggests that diverse forms of childhood maltreatment can increase risk for revictimization (e.g., Widom et al, 2008).…”
Section: Expanding Revictimization Risk Beyond Csamentioning
confidence: 99%
“…The extent to which continued victimization is a substantial problem for child sexual abuse survivors also remains a bit unclear because much of what we know about revictimization rates comes from retrospective studies of adult victims recalling childhood sexual abuse (e.g., Arata, 1999; Cloitre, Cancienne, Brodsky, Dulit, & Perry, 1996; Merrill et al, 1999; Stermac, Reist, Addison, & Millar, 2002; Urquiza & Goodlin-Jones, 1994). Limitations of retrospective studies include (1) cross-sectional designs which make the temporal distinction of events difficult to ascertain (e.g., Arata, 2000; Classen, Field, Koopman, Nevill-Manning, & Spiegel, 2001; Koss & Dinero, 1989; Maker et al, 2001; Mandoki & Burkhart, 1989; Mayall & Gold, 1995), (2) the absence of childhood abuse substantiation and/or corroboration with social services (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have found that younger women are at a higher risk for victimization than older women (O'Donnell, Smith, & Madison, 2002;US Department of Justice, 1998) and African American women are more likely than any other group of women to experience intimate partner violence (US Department of Justice, 2000b), this relationship between race and risk for victimization disappears once other individual and community level factors are included (Lauritsen & White, 2001). Prior victimization, including experiencing abuse as a child, has been associated with an increased risk for subsequent victimization (Gidycz, Hanson, & Layman, 1995;Mandoki & Burkhart, 1989;Stermac, Reist, Addison, & Millar, 2002). Stermac et al (2002) found that childhood maltreatment, including sexual abuse by an adult and neglect by a mother, increases a woman's likelihood for sexual victimization later in life.…”
Section: Correlates and Risk Factors Of Victimizationmentioning
confidence: 96%
“…Prior victimization, including experiencing abuse as a child, has been associated with an increased risk for subsequent victimization (Gidycz, Hanson, & Layman, 1995;Mandoki & Burkhart, 1989;Stermac, Reist, Addison, & Millar, 2002). Stermac et al (2002) found that childhood maltreatment, including sexual abuse by an adult and neglect by a mother, increases a woman's likelihood for sexual victimization later in life.…”
Section: Correlates and Risk Factors Of Victimizationmentioning
confidence: 98%